Refleksi Psikologi Islami dalam Dunia Psikologi di Indonesia - Syarifan Nurjan (Postgraduate Program Magister Pendidikan Agama Islam, 2017)
Movement of Islamic psychology development is an effort that has a commitment to bring the contribution of Islam to humanity. The working of Islamic psychology is to formulate theory, whose characteristics are logical and objective (measurable). After the theory is formulated, it is ready to be researched. Here the researcher makes a hypothesis. If the results of research suitable with the theory built, then it is be a solid science and ready to be applied. The development of Islamic psychology into a scientific paradigm needed considerable time, hard effort, and the accumulation results of thought, results of research, and the results of many people's implementation. The development of Islamic psychology theory, be prosecuted that knowledge based on the Islamic view (from the holy book, the universe, and the human self) is constructed, so it can be classified into a solid science. Islamic psychology is intended to make human empowerment, so that the quality of human life increases. Islamic psychology reminds us that human should be understood as being multi-dimensional. In the perspective of Islamic psychology, humans not only physical, psychological (cognitive, affective), social, but also moral-spiritual.